Pengaruh Penambahan Serat Baja Pada Kuat Tekan Mortar - Hermanto, Bagus; Rahmawati, Cut; Zardi, Muhammad; Amin, Amri (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
Steel fibers that function as small-sized reinforcements. The purpose of this study was to analyze the physical properties of sand in the form of specific gravity, bulk density, sieve analysis, fineness modulus. And analyze the mechanical properties in the form of compressive strength. Steel fibers used with variations of 0%, 1%, 2%, and 3% of the total weight of cement with a fiber length of ± 1cm. The test objects in this study were in the form of cubes with a diameter of 5cm x 5cm x 5cm and a volume of 125cm3 with a total of 36 test objects. The results of the specific gravity examination of fine aggregates using 3 samples, namely A, B, and C, obtained an average saturated surface dry density (SSD) of 2.67, an average oven dry density of 2.56 and an average water absorption of 3.96%. The results of the bulk density examination were 1.826 kg / l. The results of sieve analysis show that the aggregate used is included in the aggregate category as sand (zone II) with a fineness modulus value of 2.86, with a fineness requirement of 1.5 - 3.8. The results of mechanical properties in the form of a pressure test on mortar at the age of 7 days experienced a decrease in succession from M0 18.24 MPa by 17.5%, 11.3%, and 7.7%, with a value of M1 15.05MPa, M2 16.19 MPa, and M3 16.84 MPa. For mortar aged 14 days also experienced a decrease in succession from M0 18.25 MPa by 9.7%, 5.6%, and 1% with a value of M1 16.48 MPa, M2 17.24 MPa, and M3 18.08 MPa, due to the Bonding Stringht mechanism. Meanwhile, for 28 day old mortar, the M0 18.48 MPa increased successively by 1.1%, 3.4% and 11.5% with values of M1 18.48 MPa, M2 19.11 MPa and M3 20.61 MPa.